2020
DOI: 10.1111/adb.12986
|View full text |Cite
|
Sign up to set email alerts
|

Daily and intermittent smoking are associated with low prefrontal volume and low concentrations of prefrontal glutamate, creatine, myo‐inositol, and N‐acetylaspartate

Abstract: Cigarette smoking is still the largest contributor to disease and death worldwide. Successful cessation is hindered by decreases in prefrontal glutamate concentrations and gray matter volume due to daily smoking. Because nondaily, intermittent smoking also contributes greatly to disease and death, understanding whether infrequent tobacco use is associated with reductions in prefrontal glutamate concentrations and gray matter volume may aid public health. Eighty‐five young participants (41 nonsmokers, 24 interm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Furthermore, in the healthy volunteer group, we found that Glu/Cr levels were significantly lower in smokers. Previous studies have shown that smokers display lower cortical glutamate levels than non-smokers [64,65]. Thus, our results may be confounded by differences in smoking levels across groups.…”
Section: Strengths and Limitationsmentioning
confidence: 76%
“…Furthermore, in the healthy volunteer group, we found that Glu/Cr levels were significantly lower in smokers. Previous studies have shown that smokers display lower cortical glutamate levels than non-smokers [64,65]. Thus, our results may be confounded by differences in smoking levels across groups.…”
Section: Strengths and Limitationsmentioning
confidence: 76%
“…Thus, our result that showed decreased rsFC between the NBM and PFC could potentially reflect the cholinergic dysfunction by cigarette smoking, which might also explain the working memory and attention decline in healthy smokers observed by previous studies ( Chamberlain et al, 2012 ; Zhang et al, 2016 ). Previous findings in healthy smokers suggested that smoking was associated with reduced brain volumes ( Gallinat et al, 2006 ; Fritz et al, 2014 ) or MR spectroscopy markers of neuronal viability ( Durazzo et al, 2016 ; Faulkner et al, 2020 ), particularly in the PFC. In addition, rsfMRI studies ( Janes et al, 2012 ) also demonstrated that PFC network interactions might serve as biomarkers for nicotine dependence severity and treatment efficacy.…”
Section: Discussionmentioning
confidence: 97%
“…Spectra were analysed using LCModel 6.3-1L, with a basis set consisting of 19 simulated spectra, as in Morgenroth et al (2019) and Faulkner et al (2021) (for the full basis set, see Supplementary Materials ). This basis set was simulated using FID appliance (FID-A) ( Simpson et al, 2017 ) for TE = 8.5 ms, magnetic field strength = ~3 T and assuming ideal radiofrequency pulses.…”
Section: Methodsmentioning
confidence: 99%
“…Outer volume suppression slabs were applied 5 mm from the edge of each side of the voxel (six slabs in total), both to suppress signals originating outside of the right medial prefrontal voxel of interest, and to minimize motion artefact effects on spectra within the voxel. Spectra were analysed using LCModel 6.3-1L, with a basis set consisting of 19 simulated spectra, as in Morgenroth et al (2019) and Faulkner et al (2021) (for the full basis set, see Supplementary Materials). This basis set was simulated using FID appliance (FID-A) (Simpson et al, 2017) for TE = 8.5 ms, magnetic field strength = ~3 T and assuming ideal radiofrequency pulses.…”
Section: Questionnaire Measuresmentioning
confidence: 99%
See 1 more Smart Citation